Friction stir processing of AZ91 hybrid composites with exfoliated multi-layered graphene: A Taguchi-Grey relational analysis - Marode, R.V. (2024)
Friction Stir Processing (FSP) involves the use of Silicon Carbide (SiC) and Graphite (Gr) nanoparticles as reinforcements to enhance the properties of AZ91 Mg alloy composites. The relationship between FSP processing parameters and surface properties of Mg alloy composites with SiC and Gr nanoparticles is poorly understood. The present study addresses this and investigates the impact of SiC and Gr volume percentages (vol), tool traverse speed (TTS), and tool rotational speed (TRS) on the corrosion behavior and microhardness of AZ91 alloy composites. FSP turns graphite into layered graphene, making it more corrosion-resistant and stronger through various strengthening mechanisms. Taguchi optimization yielded optimal settings in runs H7 (1500 rpm-20 mm/min-13 vol) and H8 (1500 rpm-40 mm/min-7 vol) for high microhardness and low corrosion rate. Conversely, runs H1 (500 rpm-20 mm/min-7 vol) and H3 (500 rpm-60 mm/min-13 vol) resulted in reduced microhardness and increased corrosion rate. Integrating Taguchi and Grey Relational Analysis (GRA) optimized the multi-objective enhancement of microhardness and corrosion resistance, achieving 3rd-level values for TRS, TTS, and vol. Notably, the reinforcement percentage, followed by TRS and TTS, simultaneously improved these responses. Â© 2023 Elsevier B.V.